The Efficacy of the Combination of Microneedling with Jessner's Plus 35% Trichloroacetic Acid Peel versus the Efficacy of the Combination of Microneedling with Platelet-rich Plasma Therapy for the Treatment of Atrophic Acne Scars: A Comparative Study - Meda Deepika; Sravan Chittla; Donakonda Swetha; Sathaiahgari Dheeraj; Bandaru Sougandhika (Wolters Kluwer Medknow Publications, 2024)
Background: Acne is a common skin condition that is prevalent in 90% of the adolescent population. Inflammatory lesions of acne may lead to scarring. Various treatment modalities such as subcision, punch excision, chemical peels, microdermabrasion, and fractional lasers have been tried for acne scars but with unsatisfactory results. Purpose: The aim of the present study is to compare the efficacy of microneedling with Jessner's plus 35% trichloroacetic acid (TCA) peel versus the efficacy of microneedling with platelet-rich plasma (PRP) therapy for the management of atrophic acne scars. Methods: Sixty patients having atrophic scars due to acne were segregated into two groups each containing 30 patients. On Group A, patients microneedling was performed at weeks 0, 6, and 12 and Jessner's plus 35% TCA peel was performed at weeks 3, 9, and 15. On Group B, patients microneedling and intradermal PRP were performed sequentially at weeks 0, 3, and 6. Patients were followed at the outset of the procedure and 24 weeks after the procedure using the Echelle d'Evaluation Clinique des Cicatrices d'acne (ECCA) score. Results: The difference in the mean ECCA score at the outset of the procedure and 24 weeks after the procedure was more in Group B as compared to Group A (47.8 ± 13.6 vs. 39.1 ± 11.4). Conclusion: The efficacy of the combination of microneedling with PRP was higher than the combination of microneedling with Jessner's plus 35%TCA peel for the treatment of atrophic acne scars.